2011
DOI: 10.1007/s00167-011-1455-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of femoral tunnel enlargement in 169 patients between single-bundle and anatomic double-bundle anterior cruciate ligament reconstructions with hamstring tendon grafts

Abstract: Prospective comparative cohort study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 43 publications
1
86
2
Order By: Relevance
“…As two different tunnels are used in tibial and femoral sides, they can't be compared with conventional single bundle technique. Kawaguchi found lesser incidence of femoral tunnel enlargement in cases of double bundle ACL reconstruction than single bundle ACL reconstruction [16] . Yoon et al found that on tibial side, between AM and PM bundles, there was significant enlargement of anteromedial bundle which was statistically significant [17] .…”
Section: Discussionmentioning
confidence: 90%
“…As two different tunnels are used in tibial and femoral sides, they can't be compared with conventional single bundle technique. Kawaguchi found lesser incidence of femoral tunnel enlargement in cases of double bundle ACL reconstruction than single bundle ACL reconstruction [16] . Yoon et al found that on tibial side, between AM and PM bundles, there was significant enlargement of anteromedial bundle which was statistically significant [17] .…”
Section: Discussionmentioning
confidence: 90%
“…Tunnel enlargement was defined as more than 2.5 mm of the drill bit size, clear enlargement as 2.5-4.5 mm and massive enlargement as more than 4.5 mm, whereas borderline enlargement was defined as 0.5-2 mm 29 . Kawaguchi et al compared femoral tunnel widening between single-bundle and anatomic double-bundle ACL reconstructions with hamstring tendon grafts 19 . The tunnel measurement was taken at the intra-articular outlet of the femoral tunnels in each plane, perpendicular to the direction of the long axis of the tunnels 19 .…”
Section: Radiographsmentioning
confidence: 99%
“…Kawaguchi et al compared femoral tunnel widening between single-bundle and anatomic double-bundle ACL reconstructions with hamstring tendon grafts 19 . The tunnel measurement was taken at the intra-articular outlet of the femoral tunnels in each plane, perpendicular to the direction of the long axis of the tunnels 19 . Surer et al divided the longitudinal axis of the bone tunnel into three equal portions.…”
Section: Radiographsmentioning
confidence: 99%
“…Although the incidence is unknown and variable occurrence has been documented in the literature, bone tunnel widening after anterior cruciate ligament (ACL) reconstruction is well established [1,2,3,4,5,6] . It occurs predominantly during the first six months after surgery and has been documented up to two years postoperatively [1,3,7,8,9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…Some authors report a decrease in tunnel diameter three years after surgery [3] . Although many studies showed no effects of bone tunnel widening on clinical outcomes or objective laxity [3,5,8,9,11,12,13,14] , a few investigations demonstrated that it might be associated with anterior knee laxity and an early sign of graft failure [15,16] . Thus, the clinical significance of bone tunnel widening has not yet been fully established and is still unclear.…”
Section: Introductionmentioning
confidence: 99%